The Fair Value of Animal Zoo - Muhammad Fahmi; Muhammad Irsan (AIBPM Publisher, 2021)
However, the published financial statement of The Development District Company of Medan Sub Unit Zoo year 2015 and 2016 does not reflect the characteristic of appropriate qualitative financial statement yet with SAK. The animal in the zoo can be identified as company asset, but cannot be categorized yet as an asset, whether current asset, fixed asset or non-fixed asset. Another phenomenon is some animals cannot be detected their own fair value, because those animals are not for trade and have no market price. The animal has similar characteristic with fixed asset, but the estimation assessment of depreciation percentage and amortization, useful life and residue value cannot be measured yet trustfully. By the phenomenon, the problem comes up that is measurement (identification, categorization, and the assessment of economy transaction) so that it is enable for animal cannot be presented in the financial statement. Based on the observation result, it is acquired that animal collections as many as 38 animals, each consists of 20 species for aves class, 11 species for mammals and 7 species for reptile. According to UU No. 5 year 1990, PP No. 07 year 1999 and PP No. 08 year 1999 there are 21 protected animals, so that the fair value cannot be determined, but the unprotected animals and the category of cite appendix II as many as 10 animals can be determined due to enable to be traded.